PERCEIVED INFLUENCE OF PLAY ON LEARNING ACTIVITIES AMONG PUPILS IN ANAMBRA STATE - Mbachi, Roseline A.; Enemuo, Joy O.; Chigbo-Obasi, Tonia U. (Journal of Early Childhood and Primary Education, 2020)
The study examined perceived influence of play on learning activities among pupils in Anambra State. Descriptive survey research design was used for the study. Three research questions and three hypotheses were formulated to guide the study. The population of the study comprised all the 128 teachers (77 males and 51 females) from the 33 public primary schools in Njikoka L. G. A. of Anambra State. The reliability of the instrument was obtained using Cronbach Alpha method which yielded 0.82. An item structured questionnaire was developed and used for data collection. Mean and standard deviation were used to answer the research questions while t-test was used to test the null hypotheses. The null hypotheses were tested at 0.05 level of significance. Major findings revealed that play is one of the essential ways pupils learn problem-solving skills, develop their self-confidence, develop their cognitive skills by introducing them to new ideas, absorb experience into existing schema and develop mental capacity to improve learning performance. It was therefore recommended among others that Anambra State Government, through the academic planners should integrate appropriate play such as structured, unstructured and risky play in their curriculum development to enhance learning. Teachers should also be exposed to training on learning activities in order to up-date their skills and knowledge on organizing play suitable for pupils.